Thermal conversion and green utilisation of Chinese oil shale - Meng, Yang (2020)
Oil shales are widely defined as fine-grained sedimentary rocks containing a considerable amount of organic matters, known as kerogen. Through retorting, oil shale could be thermally converted to shale oil, which makes utilisation a possibility. The shale oil production is largely governed by the kerogen content, as well as the interactions between kerogen and mineral matrix. To clarify these phenomena, the AGR experiments were carried out using six Chinese oil shales from different regions distributed in Northeast China, namely Fushun (FS), Xingsheng (XS), Xinghua (XH), Laoheishan (LHS), Jinzhou (JZ) and Wulin (WL) oil shale. Compared with coal or biomass, these samples are predominantly comprised of quartz and clays, which together make up to approximately 50-80 wt%. Economically, it requires more energy to process oil shale during aboveground retorting (AGR), hence less profit. From an environmental viewpoint, a sufficient amount of solid wastes containing organic residues would induce unique challenges in disposal. To maximise the use of oil shales, this project aims to (1) characterise physicochemical properties of oil shale; (2) develop advanced thermal conversion technologies; (3) explore the potential of co-gasification with coal and (4) synthesise value-added nanoparticles from oil shale wastes.